Staff perception on biomedical or health care waste management: a qualitative study in a rural tertiary care hospital in India. - Sudhir Chandra Joshi; Vishal Diwan; Ashok J Tamhankar; Rita Joshi; Harshada Shah; Megha Sharma; Ashish Pathak; Ragini Macaden; Cecilia Stålsby Lundborg (PLoS ONE, 2015)
Health care or biomedical waste, if not managed properly, can be of high risk to the hospital staff, the patients, the community, public health and the environment, especially in low and middle income settings where proper disposal norms are often not followed. Our aim was to explore perceptions of staff of an Indian rural tertiary care teaching hospital on hospital waste management.A qualitative study was conducted using 10 focus group discussions (FGDs), with different professional groups, cleaning staff, nurses, medical students, doctors and administrators. The FGD guide included the following topics: (i) role of Health Care Waste Management (HCWM) in prevention of health care associated infections, (ii) awareness of and views about HCWM-related guidelines/legislation, (iii) current HCWM practices, (iv) perception and preparedness related to improvements of the current practices, and (v) proper implementation of the available guidelines/legislation. The FGDs were recorded, transcribed verbatim, translated to English (when conducted in Hindi) and analysed using content analysis.Two themes were identified: Theme (A), 'Challenges in integration of HCWM in organizational practice,' with the categories (I) Awareness and views about HCWM, (II) Organizational practices regarding HCWM, and (III) Challenges in Implementation of HCWM; and Theme (B), 'Interventions to improve HCWM,' with three categories, (I) Educational and motivational interventions, (II) Organizational culture change, and (III) Policy-related interventions.A gap between knowledge and actual practice regarding HCWM was highlighted in the perception of the hospital staff. The participants suggested organizational changes, training and monitoring to address this. The information generated is relevant not merely to the microsystem studied but to other institutions in similar settings.